2007
DOI: 10.1002/jbm.a.31307
|View full text |Cite
|
Sign up to set email alerts
|

Alginate/lactose‐modified chitosan hydrogels: A bioactive biomaterial for chondrocyte encapsulation

Abstract: A new bioactive scaffold was prepared from a binary polysaccharide mixture composed of a polyanion (alginate) and a polycation (a lactose-modified chitosan, chitlac). Its potential use for articular chondrocytes encapsulation and cartilage reconstructive surgery applications has been studied. The hydrogel combines the ability of alginate to act as a 3D supporting structure with the capability of the second component (chitlac) to provide interactions with porcine articular chondrocytes. Physico-chemical charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 48 publications
1
95
0
Order By: Relevance
“…In another study, only 26% chondrocyte viability was observed in photopolymerized gelatin gels [Hoshikawa et al, 2006]. However, other groups have reported greater than 95% chondrocyte viability [Wang et al, 2003;Marsich et al, 2008]. It has been shown previously that thrombin can affect cell growth by inducing apoptosis at a concentration above 1 IU/ml [Sarker et al, 1999;Zain et al, 2000], which is a likely explanation for our reduced viability following encapsulation (initially 98% viable).…”
Section: Discussionmentioning
confidence: 54%
“…In another study, only 26% chondrocyte viability was observed in photopolymerized gelatin gels [Hoshikawa et al, 2006]. However, other groups have reported greater than 95% chondrocyte viability [Wang et al, 2003;Marsich et al, 2008]. It has been shown previously that thrombin can affect cell growth by inducing apoptosis at a concentration above 1 IU/ml [Sarker et al, 1999;Zain et al, 2000], which is a likely explanation for our reduced viability following encapsulation (initially 98% viable).…”
Section: Discussionmentioning
confidence: 54%
“…Anionic alginate, which is able to form stable gels, and cationic chitosan, which is capable to overcome some of the biological limitations of alginate, are two ionic polysaccharides which proved to be favorable agents for bone tissue engineering, after mixing (Weir et al, 2005). The latter polymer has been also modified to obtain a branched derivative called chitlac (lactose-modified chitosan) which showed to be nontoxic and able to stimulate the production of aggrecan and type II collagen (Donati et al, 2007;Marsich et al, 2008). The mixture of the two polysaccharides, which were shown to give rise to synergistic interactions in solution (Donati et al, 2007), has proven to be very effective as a gel matrix for the encapsulation of chondrocytes (Marsich et al, 2008) which can be regarded as a first step toward the development of biologically active 3D scaffold from polysaccharide mixtures (Donati et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…The latter polymer has been also modified to obtain a branched derivative called chitlac (lactose-modified chitosan) which showed to be nontoxic and able to stimulate the production of aggrecan and type II collagen (Donati et al, 2007;Marsich et al, 2008). The mixture of the two polysaccharides, which were shown to give rise to synergistic interactions in solution (Donati et al, 2007), has proven to be very effective as a gel matrix for the encapsulation of chondrocytes (Marsich et al, 2008) which can be regarded as a first step toward the development of biologically active 3D scaffold from polysaccharide mixtures (Donati et al, 2007). It is therefore crucial to focus investigations onto scaffold materials and their properties.…”
Section: Introductionmentioning
confidence: 99%
“…Alginate forms spontaneous gels when exposed to divalent cations (e.g., Ca 2+ ), used as drug delivery devices, wound healing dressings, and tissue engineering scaffolds [420]. For example, alginate based hydrogels are produced for the delivery of chondrocytes [421], osteoblasts [422], myoblasts [423], fibroblasts, and keratinocytes [424]. In addition, alginate is also available as composite systems in which it is associated with polyesthers [425], polyethers [426], collagen [427], and CS [428] to effectively deliver drugs or proteins [429] and to form scaffolds composed of films, sponges, fibers, gels, and freeze casted porous networks used in regenerative engineering [430,431].…”
Section: Proteins and Poly(amino Acids)mentioning
confidence: 99%